Migrant-ready? The benefit of the Recognition Act for companies - Englmann, Bettina [Verfasser] (My University, 2013)
"According to the 2011 labour-market report from the German Association of Chambers of Industry and Commerce (DIHK Arbeitsmarktreport 2011), the number of companies seeing a skills shortage as one of the greatest economic risks has doubled since 2010. To tackle this problem, companies are weighing up a variety of strategies including stepping up the recruitment of skilled migrants already resident in Germany as well as potential future immigrants. The questions pursued in this article are to what extent human resources management in companies is attuned to this group of employ ees, and how the new Recognition Act can help companies in the recruitment, employment and individual support of qualified skilled workers with biographies involving migration." (Autorenreferat, BIBB-Doku)
Keywords: S 2.1 Rechtliche Regelungen in der Berufsbildung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 3.2 Unternehmen und Behörden; P 1.5 Migranten; Anerkennungsgesetz; Auslandsqualifikation; Unternehmen; Personalmanagement; Migrant